A meta-analysis of the intervention effect of mindfulness training on athletes’ performance - Si, Xing Wei; Yang, Zhen Kun; Feng, Xia (Frontiers in Psychology, 2024)
Objective To explore the intervention effect of mindfulness training on athletes’ performance using meta-analysis method. Methods A total of 11 articles and 23 effect sizes were included through retrieval of Chinese and English databases, with a total sample size of 582. Result Mindfulness training improves the level of mindfulness [SMD =1.08, 95%CI (0.30, 1.86), p < 0.01], fluency (The optimal competitive psychological state of the athlete, the athlete’s attention is all focused on the task, and other things no longer attract their attention) [SMD =1.47, 95%CI (0.87, 2.08), p < 0.001] and performance [SMD =0.92, 95% CI (0.40, 1.43), p < 0.01], reduced psychological anxiety [SMD = -0.87, 95% CI (−1.54, −0.20), p < 0.05], and all reached the level of large effect size. Conclusion The effect of mindfulness training on athletes’ sports performance is effective, and it can be used as an effective psychological skill intervention method to improve athletes’ sports performance. In the future, we should further expand the sample size, strengthen the comparative study of different sports and intervention modes, and pay attention to the difference between the time effect and trait mindfulness level in fluency state.